2018
DOI: 10.1242/jeb.184655
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the role of Rh protein in ammonia excretion of swimming crab Portunus trituberculatus

Abstract: In , a full-length cDNA of Rhesus-like glycoprotein (Rh protein), encoding the entire 478 amino acid protein, has been identified in gills, and plays an essential role in ammonia (NH/NH ) excretion. Phylogenetic analysis of Rh-like proteins from crabs was clustered, showing high conservation of the ammonium transporter domain and transmembrane segments essential to the function of Rh protein. Rh protein of (Rh) was detected in all tested tissues, and showed the highest expression in the gills. To further chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 73 publications
(87 reference statements)
1
20
0
Order By: Relevance
“…However, based on family members that have been functionally characterized, specificity is high for the target substrate, and not for other monocationic cations, at least in plants and yeast [115]. In contrast to Amt and Mep, findings are less clear for Rh proteins [116], which have also been implicated in CO 2 transport [117,118]. Rhesus factor proteins have mostly been found in eukaryotes, of which those of mammalian origin have been most studied [110,111].…”
Section: Discussionmentioning
confidence: 99%
“…However, based on family members that have been functionally characterized, specificity is high for the target substrate, and not for other monocationic cations, at least in plants and yeast [115]. In contrast to Amt and Mep, findings are less clear for Rh proteins [116], which have also been implicated in CO 2 transport [117,118]. Rhesus factor proteins have mostly been found in eukaryotes, of which those of mammalian origin have been most studied [110,111].…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al (2015) suggested that carbonic anhydrase is involved in the response to changes in pH and in systemic acid-base balance in freshwater crayfish. Ammonium transporter Rh involved in the ammonia excretory process have been identified in crustaceans (Si et al, 2018). It has been reported that the expression of Rh protein increased significantly in the gill of Eriocheir sinensis, Portunus trituberculatus, and L. vannamei after abiotic stress, and ammonia excretion was inhibited after Rh protein knockdown in Caenorhabditis elegans and P. trituberculatus (Martin et al, 2011;Ren et al, 2015;Aida et al, 2016;Si et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ammonium transporter Rh involved in the ammonia excretory process have been identified in crustaceans (Si et al, 2018). It has been reported that the expression of Rh protein increased significantly in the gill of Eriocheir sinensis, Portunus trituberculatus, and L. vannamei after abiotic stress, and ammonia excretion was inhibited after Rh protein knockdown in Caenorhabditis elegans and P. trituberculatus (Martin et al, 2011;Ren et al, 2015;Aida et al, 2016;Si et al, 2018). The Na + /H + exchanger in gill cells creates an electrochemical gradient for regulation osmotic pressure, which can help aquatic organisms balance the changes of osmotic pressure in vivo (Castaldo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple and pairwise alignments performed using the ClustalW and DNASIS programs (not presented) also confirms the significant similarity of these transporter structures. The amino acid sequence similarity of all ammonia transporters ranges from 15 to 92% for different species, with stable preservation of the topology of conservative functional sites (Si et al 2018).…”
Section: Structural and Functional Homology Of Ammonia Transporters Amentioning
confidence: 99%